META ANALISIS PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MEMECAHKAN MASALAH FISIKA PESERTA DIDIK - Wahyuni Satria Dewi; Reynaldy Siregar; Amali Putra; Hidayati Hidayati (Postgraduate, University of Mataram, 2023)
In the 21st century, the improvement of science and technology leads humans to master various skills, one of which is problem solving. Physics learning can be one of the means in improving students' problem-solving ability (PSA). The purposes of this research are determine the effect of PBL model on students' physics PSA, determine the effect of PBL model on students' physics PSA based on subject matter, and determine the effect of PBL model on students' physics PSA based on teaching materials. This research is a meta-analysis by analysing 17 articles from national journals indexed at least Sinta 4 and international journals or proceedings. The results showed that there is an effect of PBL model on the ability to solve physics problems of students as a whole equal to 1.985 with a very high category. Based on the subject matter, the most effective effect of PBL on PSA is on temperature and heat material which is 4.135 with a very high category. In the material of effort and energy, the influence of PBL on PSA is the lowest compared to other materials with an effect size value of 0.365. While based on teaching materials, the effect of PBL on physics PSA is low with an effect size of 0.315. Digital teaching materials are the best teaching materials applied in PBL learning to improve students' physics PSA